Design and realization of a reconfigurable low complexity spectrum detector for cognitive radios - Lin, Mengda. (2012)
Cognitive radio (CR) has been proposed as a dynamic and adaptive spectrum sharing paradigm which will give opportunistic access of the vacant frequency bands to a group of users called cognitive radio users (secondary users) for whom the band has not been licensed. Fast and accurate spectrum sensing (spectrum detection) is important in CR to perform signal detection and spectral analysis with a low probability of interception (LPI). The spectrum sensor in a CR should be able to support different detection requirements such as sensing resolution (sensing resolution is defined as analysis resolution or step-size in frequency domain) and detection bandwidth (i.e. the total input bandwidth for detection) due to the wide variation of the input signal. Thus reconfigurability is one of the key requirements in the spectrum detector for CR. Conventional discrete Fourier transform (DFT) based filter bank spectrum detector is not an optimum solution for such scenarios due to its fixed uniform bandwidth and high power consumption. Dynamic sensing configuration of a DFT based filter bank spectrum detector for achieving different sensing resolutions will consume substantial hardware overhead. The design and realization of a spectrum detector that offers an efficient trade-off between area consumption, power consumption, and reconfigurability is highly significant in the current scenario. This thesis addresses the issue of incorporating low complexity and reconfigurability into the spectrum detector for CR receiver.